2018
DOI: 10.1371/journal.pone.0200779
|View full text |Cite
|
Sign up to set email alerts
|

At similar weight loss, dietary composition determines the degree of glycemic improvement in diet-induced obese C57BL/6 mice

Abstract: BackgroundAchieving weight loss is the cornerstone of the treatment of the metabolic consequences of obesity, in particular of glucose intolerance.ObjectiveTo determine whether improvement in glucose control depends on dietary macronutrient composition of the diet at identical weight loss.Materials and methodsTwenty-two weeks old diet-induced obese C57BL/6 mice lost weight through caloric restriction on normal chow (R-NC) or high fat diet (R-HF). Control mice were fed normal chow (LEAN) or high fat diet (OBESE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…It is likely that CR-induced loss of body fat was a key factor promoting better glucose control irrespective of the dietary carbohydrate and fat content. In contrast to our findings, a recent CR study of C57BL/6 mice showed a smaller improvement in glucose tolerance for a high-fat diet compared with chow diet, which is high in carbohydrates, in spite of similar weight loss for both diets (27). However, macronutrients and their sources were not strictly controlled in the latter study, and the protein content differed substantially between both diets (i.e., 20% of kilocalories for high-fat diet and 33% of kilocalories for chow diet low in fat).…”
Section: Original Articlecontrasting
confidence: 99%
See 1 more Smart Citation
“…It is likely that CR-induced loss of body fat was a key factor promoting better glucose control irrespective of the dietary carbohydrate and fat content. In contrast to our findings, a recent CR study of C57BL/6 mice showed a smaller improvement in glucose tolerance for a high-fat diet compared with chow diet, which is high in carbohydrates, in spite of similar weight loss for both diets (27). However, macronutrients and their sources were not strictly controlled in the latter study, and the protein content differed substantially between both diets (i.e., 20% of kilocalories for high-fat diet and 33% of kilocalories for chow diet low in fat).…”
Section: Original Articlecontrasting
confidence: 99%
“…The main aim of our study was to investigate whether the carbohydrate and fat content of diets affects physiological responses to CR in mice. Most of the previous studies have focused on effects of macronutrient content of diets on health and body composition in ad libitum–fed mice (19,26), and there have been only a few studies under conditions of CR (27). In agreement with recent findings on humans undergoing mild CR (28), our results show that improvements in body composition and glucose tolerance do not differ between low‐fat and low‐carbohydrate diets with similar protein content under conditions of up to 40% CR.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a high-fat diet with caloric restriction had a positive effect on plasma adipokine levels, glucose tolerance, lipid profile, and inflammation and oxidative stress in rats [6]. Other studies also confirm that the type of diet is one of the most important factors that can influence inflammation, metabolic responses, and behavior, including dietary habits [7][8][9][10].…”
Section: Introductionmentioning
confidence: 85%
“…All three diets promoted improvements in glucose tolerance during caloric restriction compared to obese controls, but low-carbohydrate diet tended to have a smaller effect compared to the other diets. Impaired glucose tolerance with low-carbohydrate and/or ketogenic diets was linked to reduced α- and β-cell mass leading to decrease in insulin synthesis and secretion in rodents [ 39 , 40 , 41 , 42 , 43 , 44 ]. Humans adapted to low-carb-high-fat diet had lower skeletal muscle GLUT4 and IRS1 contents which was linked to reduced their glucose tolerance [ 45 ].…”
Section: Discussionmentioning
confidence: 99%